Prognostic significance of right ventricle size and function in dilated cardiomyopathy. (4th February 2022) - Dziewiecka, E; Karabinowska, A; Wisniowska-Smialek, S; Winiarczyk, M; Gliniak, M; Robak, J; Kaciczak, M; Rubis, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Dilated cardiomyopathy (DCM) is diagnosed based on systolic dysfunction and dilatation of the left ventricle (LV). Although the right ventricle (RV) can be also affected, the significance of concomitant RV pathology in DCM is less studied. Aim: To analyse the prognostic significance of RV dilatation (RVD) and RV systolic dysfunction (RVSD) in DCM. Methods: Between 2010 and 2020 we retrospectively analysed out- and in-hospital records of 545 DCM patients (age 53 ± 13 years, 89% male, NYHA 2.4 ± 0.9, LV end-diastolic diameter 65 ± 10mm, LV ejection fraction - LVEF 27 ± 11%, RV outflow tract diameter - RVOT 33 ± 7mm, tricuspid annular plane systolic excursion - TAPSE 19 ± 5mm). The RVD was diagnosed as RVOT from parasternal long-axis view >35mm, and RVSD - as TAPSE <17mm. Results: There were 284 (52%) patients with RV pathology: 192 (35%) PTS with RVD, 175 (32%) patients with RVSD, 83 (15%) patients had both RVD and RVSD (RVD + RVSD). During 47 ± 31months 83 (15%) patients died: 20 (24%) patients with RVD (p = 0.007), 32 (18%) patients with RVSD (p = 0.08), 39 (11%) patients with both RVD and RVSD (p = 0.002). All RV pathologies were found to be significant prognostic factors in DCM (RVD: HR 0.41 [95%CI 0.27-0.65]; RVSD: HR 0.59 [95%CI 0.38-0.93]; RVD + RVSD: HR 0.40 [95%CI 0.24-0.67]) (Fig. 1). However, only RVD was found to be significant prognostic factor irrespectively of LVEF (multivariate: LVEF – HR 0.97 [95%CI 0.94-0.99]; RVD – HR 0.50 [95%CI 0.31-0.79]; RVSD – HR 0.82 [9%CI 0.51-1.32]). Conclusion: Half of DCM patients had RV pathology: dilatation or systolic dysfunction, however, only 15% had both RVD and RVSD. RVD and RVSD were associated with survival, however, only RV dilatation was found to be a prognostic factor irrespectively of LVEF.